Complementation Studies of Lethal Alleles in the Mouse Causing Deficiencies of Glucose-6-Phosphatase, Tyrosine Aminotransferase, and Serine Dehydratase - Gluecksohn-Waelsch, Salome (1974)
The pleiotropic effects of six radiation-induced lethal alleles at the albino locus in the mouse include deficiencies of various enzymes and of serum proteins. Closely correlated with the biochemical deficiencies are severe ultrastructural abnormalities of endoplasmic reticulum membranes and the Golgi apparatus in liver and kidney cells. Complementation studies led to the distinction of four different complementation groups among the six lethal alleles. The results are compatible with the interpretation that the six lethal alleles represent overlapping deletions of various sizes at and around the albino locus in the mouse, in a region concerned with the control of biochemical and structural differentiation.